Philologus : Zeitschrift für antike Literatur und ihre Rezeption /A Journal for Ancient Literature and its Reception (De Gruyter (A), 1846)
Philologus is one of the oldest and most respected periodicals in the field of Classical Studies. It publishes articles on Greek and Latin literature, historiography, philosophy, history of religion, linguistics, reception, and the history of scholarship. The journal aims to contribute to our understanding of Greco-Roman culture and its lasting influence on European civilization.